Pengaruh Edukasi Berbasis Online Terhadap Pengetahuan Dan Sikap Ibu Hamil Tentang Pelayanan Maternal Dan Neonatal Di Masa Pandemi Covid-19 Di Kabupaten Sleman - Chentia Misse Issabella; Febry Heldayasari Prabandari (Journal of Health (JoH), 2021)
Pregnancy is a very happy moment. In order for a pregnancy to run well, maternal and neonatal services in health facilities are needed to ensure the safety of the mother and fetus. However, the COVID-19 outbreak has caused increased anxiety and discomfort for pregnant women in Sleman Regency. Based on a survey conducted in the month of July 2020 in Sleman Regency, there were 46 pregnant women and it was found 38 pregnant women (82,6%) experienced excessive worry due to lack of information on maternal and neonatal services during the pandemic. The purpose of this study was to determine the effect of online education on increasing knowledge and attitudes towards maternal and neonatal services during the pandemic in Sleman Regency in 2020. This study used a pre-experimental method with a sample of 60 pregnant women who were divided into 2 groups using randomization techniques. simple (simple randomization) and the Mann-Whitney test. The results of the study showed an increase in knowledge and attitudes through online education of 39,17 (post 1) dan 43,52 (post 2) level, while the group without education was 21,83 (post 1) dan 17,46 (post 2) level. From the results of the study shows the difference between groups that are given online education and lefleat on increasing knowledge and attitudes on maternal and neonatal services was 41,25 (post 1) dan 39,68 (post 2) in Sleman Regency in 2020. It is hoped that pregnant women can respond and take the best steps in maintaining health with online knowledge has been obtained.